KAJIAN KETERSEDIAAN JAGUNG DAN KEDELAI DALAM RANGKA MENGHADAPI PERDAGANGAN BEBAS: KASUS NEGARA-NEGARA ASEAN - DERMOREDJO, SAKTYANU K.; MASYHURI, MASYHURI; DARWANTO, DWIDJONO H.; MULYO, JANGKUNG H. (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2012)
Agreements in the countries of Southeast Asia for ASEAN Economic Community indicate cooperation for the future co-exists within the community towards a better welfare, especially in fulfillment of food sufficiency. Stable food supply is a priority in the national food security. This paper aims to analyze the relationship between the stock of corn and soybeans in relation to macro conditions ASEAN region.